Butylated hydroxytoluene enediyne: access to diradical and electrophilic quinone methide intermediates. (2nd March 2015) - Greer, Edyta M.; Quezada, Cesar S.; Cosgriff, Christopher V.
Abstract : A theoretical study was carried out on the unimolecular reaction of an enediyne with a fused butylated hydroxytoluene to internally scavenge the p ‐benzyne diradical sites formed after theBergman cyclization . The calculations revealed that the conversion of the p ‐benzyne diradical (2‐ tert ‐butyl‐4‐methyl‐5, 8‐didehydro‐1‐naphthalenol) to p ‐quinone methide is favored over the conversion to a phenoxy/benzene diradical 4 in an approximate 95:5 ratio. Based on this model, theBergman cyclization leads in a bifunctional manner to intermediates for competing reactivity withintermolecular H‐atom abstraction. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The Bergman cyclization was theoretically studied with an enediyne fused to a butylated hydroxytoluene (di)radical scavenger.